2002
DOI: 10.1080/003655902320131875
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis and the Effective Factors

Abstract: As enuresis is rather widespread, the parents may consider this as a transient problem and therefore no effort might be given for the solution. Trained health personnel and physicians should enlighten the parents about enuresis in order to eliminate the negative effect on the child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 4 publications
2
17
0
2
Order By: Relevance
“…PNE is a frequently seen disorder in Turkish children at primary school ages, with a frequency of 20%. It is also reported that the frequency is greater in male children [4][5][6]. The children participating in our study were mostly male, too (57.8%).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…PNE is a frequently seen disorder in Turkish children at primary school ages, with a frequency of 20%. It is also reported that the frequency is greater in male children [4][5][6]. The children participating in our study were mostly male, too (57.8%).…”
Section: Discussionsupporting
confidence: 51%
“…In an epidemiological study conducted by Cher et al [17] in Taiwan, it was observed that low socioeconomic status and wide family structures may be factors of risk for PNE. In a study by Akis et al [4] in Turkey, it was shown that PNE is more frequent in children of young working mothers of low educational background. In a study from Italy, it was reported that low socio-economic status of the family, low birthweight and male sex were risk factors for enuresis [5].…”
Section: Discussionmentioning
confidence: 96%
“…Of these 1021 women, 229 (22.4%) had a history of NE in childhood; in these 229 the frequency of childhood NE in 28 (12.2%) was daily, in 33 (14.4%) 'once a week', in 21(9.2%) 'more than once a week', in 51(22.3%) 'once a month' and in 96 (41.9%) 'less than once a month' . The mean age when the NE in childhood resolved was 9.33 (2.39, [6][7][8][9][10][11][12][13][14][15][16] years. The rates of childhood NE in the subgroups of UI are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The disorder ultimately impacts the children's social life and causes secondary emotional and learning problems. Different pathological mechanisms were postulated as possible causative factors including genetic predisposition, sleep disturbance, environmental, behavioural or psychological problems as well as voiding dysfunction (1)(2)(3)(4). Many epidemiological studies of enuresis have shown to vary in different areas and countries (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%